Building a Strong Indonesian Defense through the National Value of Saladin Al-Ayyubi in the Face of 21st Century Proxy Wars - Patmi, Sri; Susmoro, Harjo; Prakoso, Lukman Yudho; Aliyah, Yurizki (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to analyze the national value of Saladin Al-Ayyubi in the face of 21st century proxy wars. The method used is qualitative descriptive using Milles, Huberman and Saldana (2014) analysis techniques, namely data collection, data condensation, presenting data (data display), and drawing conclusions or verification (conclusion drawing and verification). The validity test of the data used is Credibility (Internal Validity), Transferability (External Validity), Dependability (Reliability) and Confirmability (Objectivity). The findings of this study are aspects of leadership and integrity of character consisting of assertiveness and courage, simplicity and humility. Indonesian leaders must be firm and courageous in making decisions, including in the face of proxy threats. Courage is also needed in countering propaganda and radicalism that can trigger internal conflicts.